Dynamic and Robust Streaming in and between Connected Consumer-Electronic Devices - Stok, Peter van der (Philips Research Book Series, 2005)
Dynamic and Robust Streaming in and between Connected Consumer-Electronic Devices addresses a subject that is becoming more important over the years. On the one hand the arrival of home networks is imminent, and on the other hand we notice that chips integrate more and more functionality. The home network interconnects the Consumer Electronic (CE) devices in the home, and the individual CE-devices incorporate the chips to realize a ubiquitous streaming of video streams over this network. This book provides a comprehensive overview of the challenges that face us. The book shows that there are many similarities between traditional networking and networks in the chip. However, there are some different operational conditions that lead to original solutions. Dynamic and Robust Streaming in and between Connected Consumer-Electronic Devices focuses on the robustness aspects of the chosen technologies in the area of video streaming. Management of resources such as memory, bandwidth, CPU cycles, bus-cycles is an aspect that is prominent in many of the sections.